Perception versus reality: Does provider documentation behavior change when clinic notes are shared electronically with patients?. (January 2021) - Richards, Sarah; Carlson, Kristy; Matthias, Tabatha; Birge, Justin
Abstract: Introduction: Secure patient portals have improved patient access to information, including provider notes. Although there is evidence suggesting that electronic note sharing improves communication and care quality, some studies have reported provider concerns regarding note sharing. Material and methods: This mixed-methods single site study utilized survey questions from a previously published landmark study to assess provider perceptions of electronic note sharing as well as objective EHR data. Surveys were sent to 628 providers in 34 primary and specialty care clinics approximately 12 weeks after the implementation of phase 1 (April 1, 2018) and phase 2 (July 1, 2018). EHR data were extracted from three months pre- and three months post-implementation of note sharing to determine whether or not note authoring times were affected. Results: Nearly one-quarter ( n = 150) of the responses sent to 628 providers were retained for analysis (23.9 % response rate). A majority (84.7 %) of respondents believed notes were useful vehicles for communication and 73.3 % agreed that making notes available to patients was a good idea. Additionally, 16.0 % of respondents (14.0 % for primary care and 17.0 % for specialists) believed they "spent more time writing/dictating/editing their notes." A comparison of pre-post note authoring time revealed the aggregated primary care median increased 0.14 min (7.93–8.07 min) while aggregated specialty care median was identical (11.6 min). Discussion: The EHR comparison of note authoring time pre-post did not reflect provider concerns identified in the survey regarding electronic note sharing.